Social Media Marketing: Strategies and Impact on Business - Ballabh , Samita (Gyan Management Journal, 2023)
This paper aims to explore the field of social media marketing for businesses. Individuals use social media to stay in contact with friends, family and communities at large. Businesses of all kinds and sizes use social media to interact with customers and promote their brand at a relatively low cost. In today’s digital era, social media platforms have revolutionized the way businesses engage with their target audience, build brand awareness and promote their products and services. The study delves into various strategies used in social media marketing such as selecting the right platform, creating compelling content, leveraging influencer collaborations and enhancing customer engagement. Additionally, the paper attempts to compare the effectiveness and impact of social media marketing with traditional marketing methods. For this purpose, a descriptive research approach was employed, utilizing secondary data. The research findings provide valuable insights into the significance of social media marketing as a powerful tool for businesses, especially micro and small enterprises to reach and engage with their customers. By embracing the power of social media marketing, businesses can effectively reach their target audience and stay competitive in this digital age.